Nested Equilateral Triangles and Circles

Geometry Level 3

Starting with equilateral A B C \triangle{ABC} the diagram above illustrates nested circles and equilateral triangles. Let A T ( n ) A_{T}(n) and A c ( n ) A_{c}(n) be the areas of the n n th equilateral triangle and the n n th circle respectively.

If n = 1 ( A T ( n ) + A c ( n ) ) A T ( 1 ) = a ( b b + π ) b 2 b \dfrac{\sum_{n = 1}^{\infty} \left(A_{T}(n) + A_{c}(n)\right)}{A_T(1)} = \dfrac{a(b\sqrt{b} + \pi)}{b^2\sqrt{b}} , where a a and b b are coprime positive integers, find a + b a + b .


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 21, 2019

Let O O be the centroid of the first equilateral A B C \triangle ABC and M M be the midpoint of A C AC . Then the medium B M BM passes through O O and is perpendicular to A C AC . Since O O is the centroid, B O = 2 O M BO=2OM .Therefore the linear dimension of the second triangle is half that of the first, and the third's is half of the second's and so on. Hence the area of n n th triangle and incircle are 1 4 \frac 14 that of the preceding ( n 1 ) (n-1) th ones respectively.

That is A T ( n ) = 1 4 A T ( n 1 ) A_T(n) = \dfrac 14 A_T(n-1) A T ( n ) = A T ( 1 ) 4 n 1 \implies A_T(n) = \dfrac {A_T(1)}{4^{n-1}} . Similarly, A c ( n ) = A c ( 1 ) 4 n 1 A_c(n) = \dfrac {A_c(1)}{4^{n-1}} .

Then we have:

n = 1 ( A T ( n ) + A c ( n ) ) A T ( 1 ) = 1 A T ( 1 ) n = 1 ( A T ( 1 ) 4 n 1 + A c ( 1 ) 4 n 1 ) = A T ( 1 ) + A c ( 1 ) A T ( 1 ) n = 0 ( 1 4 ) n = ( 1 + π 3 3 ) 1 1 1 4 Note that A c ( 1 ) A T ( 1 ) = π 3 3 = 4 ( 3 3 + π 9 3 \begin{aligned} \frac {\sum_{n=1}^\infty \left(A_T(n) + A_c(n)\right)}{A_T(1)} & = \frac 1{A_T(1)} \sum_{\color{#3D99F6}n=1}^\infty \left(\frac {A_T(1)}{4^{\color{#3D99F6}n-1}} + \frac {A_c(1)}{4^{\color{#3D99F6}n-1}} \right) \\ & = \frac {A_T(1)+A_c(1)}{A_T(1)} \sum_{\color{#D61F06}n=0}^\infty \left(\frac 14\right)^{\color{#D61F06}n} \\ & = \left(1+\color{#3D99F6} \frac \pi{3\sqrt 3}\right) \frac 1{1-\frac 14} & \small \color{#3D99F6} \text{Note that }\frac {A_c(1)}{A_T(1)} = \frac \pi{3\sqrt 3} \\ & = \frac {4(3\sqrt 3+\pi}{9\sqrt 3} \end{aligned}

Therefore, a + b = 4 + 3 = 7 a+b = 4+3 = \boxed 7 .

Rocco Dalto
Jan 20, 2019

Let a 1 a_{1} be a side of equilateral A B C \triangle{ABC} .

A T 1 = 3 4 a 1 2 A_{T_{1}} = \boxed{\dfrac{\sqrt{3}}{4}a_{1}^2}

a 1 2 = 3 2 m 1 m 1 = a 1 3 h 1 = a 1 2 3 A c ( 1 ) = π 12 a 1 2 = π 4 3 \dfrac{a_{1}}{2} = \dfrac{\sqrt{3}}{2}m_{1} \implies m_{1} = \dfrac{a_{1}}{\sqrt{3}} \implies h_{1} = \dfrac{a_{1}}{2\sqrt{3}} \implies A_{c}(1) = \dfrac{\pi}{12}a_{1}^2 = \boxed{\dfrac{\pi}{4 * 3}}

a 2 2 = 3 2 h 1 a 2 = 3 h 1 = 3 ( a 1 2 3 ) = a 1 2 \dfrac{a_{2}}{2} = \dfrac{\sqrt{3}}{2}h_{1} \implies a_{2} = \sqrt{3}h_{1} = \sqrt{3}(\dfrac{a_{1}}{2\sqrt{3}}) = \dfrac{a_{1}}{2} and h 2 = 3 2 a 2 = 3 2 ( a 1 2 ) = 3 4 a 1 A T 2 = 3 16 a 1 2 = 3 4 2 a 1 2 h_{2} = \dfrac{\sqrt{3}}{2}a_{2} = \dfrac{\sqrt{3}}{2}(\dfrac{a_{1}}{2}) = \dfrac{\sqrt{3}}{4}a_{1} \implies A_{T_{2}} = \dfrac{\sqrt{3}}{16}a_{1}^2 = \boxed{\dfrac{\sqrt{3}}{4^2}a_{1}^2}

a 2 2 = 3 2 m 2 m 2 = a 2 3 = a 1 2 3 \dfrac{a_{2}}{2} = \dfrac{\sqrt{3}}{2}m_{2} \implies m_{2} = \dfrac{a_{2}}{\sqrt{3}} = \dfrac{a_{1}}{2\sqrt{3}} \implies h 3 = 1 2 ( a 1 2 3 ) = a 1 4 3 h_{3} = \dfrac{1}{2}(\dfrac{a_{1}}{2\sqrt{3}}) = \dfrac{a_{1}}{4\sqrt{3}} A c 2 = π 4 2 3 a 1 2 \implies A_{c_{2}} = \boxed{\dfrac{\pi}{4^2 * 3}a_{1}^2}

Continuing in this manner we have:

A T ( n ) = 3 4 n a 1 2 \boxed{A_{T}(n) = \dfrac{\sqrt{3}}{4^n}a_{1}^2} and A c ( n ) = π 3 4 n a 1 2 \boxed{A_{c}(n) = \dfrac{\pi}{3 * 4^n}a_{1}^2}

T = n = 1 A T ( n ) + A c ( n ) = 1 4 ( 3 3 + π 3 ) a 1 2 n = 1 1 4 n 1 = 1 4 ( 3 3 + π 3 ) a 1 2 ( 4 3 ) a 1 2 = T = \sum_{n = 1}^{\infty} A_{T}(n) + A_{c}(n) = \dfrac{1}{4}(\dfrac{3\sqrt{3} + \pi}{3})a_{1}^2 \sum_{n = 1}^{\infty} \dfrac{1}{4^{n - 1}} =\dfrac{1}{4}(\dfrac{3\sqrt{3} + \pi}{3})a_{1}^2(\dfrac{4}{3})a_{1}^2 = ( 3 3 + π 9 ) a 2 2 (\dfrac{3\sqrt{3} + \pi}{9})a_{2}^2

and

T A T 1 = 4 ( 3 3 + π ) 9 3 = a ( b b + π ) b 2 b a + b = 7 \dfrac{T}{A_{T_{1}}} = \dfrac{4(3\sqrt{3} + \pi)}{9\sqrt{3}} = \dfrac{a(b\sqrt{b} + \pi)}{b^2\sqrt{b}} \implies a + b = \boxed{7}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...